The effect of transfer pricing on tax avoidance on transport and logistics sector companies listed on Indonesia Stock Exchange in 2019 – 2022 - Anna Altahea Arthic; Marthinus Ismail (Jurnal Mantik, 2023)
This study aims to determine the effect of transfer prices on tax avoidance. This type of research is quantitative. The data used in this study are secondary data. The population in this study is service companies listed on the Indonesia Stock Exchange in the transportation and logistics sector in 2019–2022. The total population in this study was 30 companies. The sampling technique used purposive sampling and obtained as many as 24 companies with a research period of 4 years, so that 96 sample data points were obtained. The data analysis used in this study is descriptive analysis, classical assumption testing, correlation coefficients, determination coefficients, significance tests, and regression analysis.